Globalization and contemporary Islamic thought, analysis and vision (Journal of the College of Basic Education, 2022)
With the beginnings of the Islamic renaissance, Muslims found themselves facing many major thesesWhich has its dominance over the global culture and which puts them in a position to react negatively towards itBecause it is a Western product, it was associated in the Islamic consciousness with disbelief, colonialism, and domination over its potential.